The Manual of the law of armed conflict - Great Britain. Ministry of Defence (New York : Oxford University Press, 2004)
This work provides a full-scale tri-service official UK military manual on the international law of armed conflict. Topics covered include conduct of hostilities, intervention in civil wars, neutrality and environmental considerations.
Ch. 1. Historical and general background -- Ch. 2. Basic principles of the law of armed conflict -- Ch. 3. The applicability of the law of armed conflict -- Ch. 4. The armed forces of the belligerents -- Ch. 5. The conduct of hostilities -- Ch. 6. Weapons -- Ch. 7. The wounded, sick, and dead and medical services -- Ch. 8. Prisoners of war -- Ch. 9. Protection of civilians in the hands of a party to the conflict -- Ch. 10. Negotiations between belligerents -- Ch. 11. Occupied territory -- Ch. 12. Air operations -- Ch. 13. Maritime warfare -- Ch. 14. Application of the law of armed conflict during peace support operations -- Ch. 15. Internal armed conflict -- Ch. 16. Enforcement of the law of armed conflict -- App. A. Geneva Convention I 1949 : annexes -- App. B. Geneva Convention II 1949 : annex -- App. C. Geneva Convention III 1949 : annexes -- App. D. Geneva Convention IV 1949 : annexes -- App. E. Additional protocol I 1977 : annexes -- App. F. Hague Cultural Property Convention 1954, article 16 -- App. G. Annex to the amended mines protocol.
Keywords: War (International law)